2020
DOI: 10.1139/cjfas-2019-0202
|View full text |Cite
|
Sign up to set email alerts
|

Case studies demonstrate capacity for a structured planning process for ecosystem-based fisheries management

Abstract: Structured, systematic processes for decision-making can facilitate implementation of ecosystem-based fisheries management (EBFM). In US fisheries management, existing fishery ecosystem plans (FEPs) are primarily descriptive documents — not action-oriented planning processes. “Next-generation” FEPs extend existing FEPs by translating ecosystem principles into action through a structured process, including identifying and prioritizing objectives and evaluating trade-offs while assessing alternative management s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Inferring predator dependence on prey species through spatial overlap studies may better inform management of prey populations (Eero et al, 2012; Koehn et al, 2020). Further, understanding where and when predators aggregate in response to prey can help in assessing and managing negative interactions between predators and human activities (Santora et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Inferring predator dependence on prey species through spatial overlap studies may better inform management of prey populations (Eero et al, 2012; Koehn et al, 2020). Further, understanding where and when predators aggregate in response to prey can help in assessing and managing negative interactions between predators and human activities (Santora et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In most of the assessments considered in this review, environmental drivers consisted of a single dominant feature of the ecosystem that had undergone substantial change over the stock's history, although sometimes correlated with other features or metrics for the region of interest (e.g., climate and oceanographic indices). Many have advocated for the development of a systematic framework to ensure a comprehensive evaluation of the potential effects of anthropogenic and environmental drivers on aquatic stocks (Koehn et al, 2020; Link et al, 2020; Marshall et al, 2019) and while such proposals have often been aimed in the context of the more holistic ecosystem‐based fisheries management, which is focussed at the multispecies level, the basic principles could serve as a base for the broader application of an EAFM in the Canadian system.…”
Section: Discussionmentioning
confidence: 99%
“…States considers environmental variables in management advice through detailed Ecosystem Status Reports for large marine ecosystems (Craig et al, 2021;Ferriss & Zador, 2021;Gove et al, 2019;Harvey et al, 2021;Ortiz & Zador, 2021;Siddon, 2021). Ecosystem "report cards" or overviews are also used in Australia (Gaughan & Santoro, 2018), Europe (AORA, 2017;ICES, 2016aICES, , 2016bICES, , 2016cICES, , 2016dICES, , 2017aICES, , 2017b environmental drivers on aquatic stocks (Koehn et al, 2020;Link et al, 2020;Marshall et al, 2019) and while such proposals have often been aimed in the context of the more holistic ecosystembased fisheries management, which is focussed at the multispecies level, the basic principles could serve as a base for the broader application of an EAFM in the Canadian system.…”
Section: The Need To Move Towards Broad Application Of Eafm Principlesmentioning
confidence: 99%
“…Accounting for productivity changes (here year-class strength) is a first principle of ecosystem-based fisheries management (EBFM) and modelling studies have demonstrated that considering environmental changes can prevent fish stock collapses and can help accounting for the effects of climate change 72 75 . EBFM implementation is lacking behind in the EU compared to the United States 76 80 , while practical use of environmental information in fisheries management is deficient worldwide 81 , 82 . For example, in the advice framework for EU fish stocks, environmental context, although provided in ecosystem overviews, is still not directly incorporated in the advice.…”
Section: Discussionmentioning
confidence: 99%